Simple Quantitative Sensory Testing Reveals Paradoxical Co-existence of Hypoesthesia and Hyperalgesia in Diabetes - Hansen, Line Elise Møller; Fjelsted, Camilla Ann; Olesen, Søren Schou; Phillips, Anna Evans; Faghih, Mahya; Wegeberg, Anne-Marie; Drewes, Asbjørn Mohr; Brock, Christina (Frontiers in Pain Research, 2021)
Background: Diabetic neuropathy is characterized by the paradoxical co-existence of hypo- and hyperalgesia to sensory stimuli. The literature shows consistently sensory differences between healthy and participants with diabetes. We hypothesized that due to differences in pathophysiology, advanced quantitative sensory testing (QST) might reveal sensory discrepancies between type 1 (T1D) and type 2 diabetes (T2D). Furthermore, we investigated whether vibration detection thresholds (VDT) were associated with sensory response. Method: Fifty-six adults with T1D [43 years (28–58)], 99 adults with T2D [65 years (57–71)], and 122 healthy individuals [51 years (34–64)] were included. VDT, pressure pain detection thresholds (pPDT) and tolerance (pPTT), tonic cold pain (hand-immersion in iced water), and central pain mechanisms (temporal summation and conditioned pain modulation) were tested and compared between T1D and T2D. VDT was categorized into normal (< 18 V), intermediary (18–25 V), or high (> 25 V). Results: In comparison to healthy, analysis adjusted for age, BMI, and gender revealed hypoalgesia to tibial (pPDT): p = 0.01, hyperalgesia to tonic cold pain: p < 0.01, and diminished temporal summation (arm: p < 0.01; abdomen: p < 0.01). In comparison to participants with T2D, participants with T1D were hypoalgesic to tibial pPDT: p < 0.01 and pPTT: p < 0.01, and lower VDT: p = 0.02. VDT was not associated with QST responses. Conclusion: Participants with T1D were more hypoalgesic to bone pPDT and pPTT independent of lower VDT, indicating neuronal health toward normalization. Improved understanding of differentiated sensory profiles in T1D and T2D may identify improved clinical endpoints in future trials.